Expression of TLR4 Is Upregulated in Patients with Sporadic Acute Stanford Type A Aortic Dissection - Xinyi Liu; Ai Zhang; Nianguo Dong; Zhiwen Wang (Cardiology Research and Practice)
Sporadic acute Stanford type A aortic dissection (TAAD) is a serious condition that requires urgent treatment to avoid catastrophic consequences. The purpose of the present study was to explore, firstly, whether TLR4-regulated immune signalling molecules were activated in TAAD patients and, secondly, whether TLR4-regulated inflammatory products interleukin-1β (IL-1β) and CC chemokine ligand 5 (CCL5) could be a promising biomarker for diagnosis in patients with TAAD. Full-thickness ascending aortic wall specimens from TAAD patients (n = 12) and control donors (n = 12) were examined for the expression of TLR4 and its major signalling molecules, in terms of immunity and inflammation. Blood samples from TAAD (n = 49) and control patients (n = 53) were collected to detect the circulating plasma cytokine levels of IL-1β and CCL5. We demonstrated that expression levels of TLR4 and its downstream signalling cascade molecules were significantly elevated. Furthermore, receiver operating characteristic curve analyses showed that elevated IL-1β levels and decreased plasma CCL5 may have diagnostic value for TAAD. In summary, this current study suggests a more generalized pattern of inflammation in TAAD. In addition, TLR4-mediated inflammatory product, such as IL-1β and CCL5, could be novel and promising biomarkers with important diagnostic and predictive value in the identification of sporadic TAAD diseases.